Ca2+ handling in isolated brain mitochondria and cultured neurons derived from the YAC128 mouse model of Huntington's disease. (4th June 2015) - Pellman, Jessica J.; Hamilton, James; Brustovetsky, Tatiana; Brustovetsky, Nickolay
Abstract We investigated Ca2+ handling in isolated brain synaptic and non‐synaptic mitochondria and in cultured striatal neurons from the YAC128 mouse model of Huntington's disease. Both synaptic and non‐synaptic mitochondria from 2‐ and 12‐month‐old YAC128 mice had larger Ca2+ uptake capacity than mitochondria from YAC18 and wild‐type FVB/NJ mice. Synaptic mitochondria from 12‐month‐old YAC128 mice had further augmented Ca2+ capacity compared with mitochondria from 2‐month‐old YAC128 mice and age‐matched YAC18 and FVB/NJ mice. This increase in Ca2+ uptake capacity correlated with an increase in the amount of mutant huntingtin protein (mHtt) associated with mitochondria from 12‐month‐old YAC128 mice. We speculate that this may happen because of mHtt‐mediated sequestration of free fatty acids thereby increasing resistance of mitochondria to Ca2+‐induced damage. In experiments with striatal neurons from YAC128 and FVB/NJ mice, brief exposure to 25 or 100 μM glutamate produced transient elevations in cytosolic Ca2+ followed by recovery to near resting levels. Following recovery of cytosolic Ca2+, mitochondrial depolarization with FCCP produced comparable elevations in cytosolic Ca2+, suggesting similar Ca2+ release and, consequently, Ca2+ loads in neuronal mitochondria from YAC128 and FVB/NJ mice. Together, our data argue against a detrimental effect of mHtt on Ca2+ handling in brain mitochondria of YAC128 mice. <boxed-text content-type="graphic" id="jnc13165-blkfxd-1001" position="anchor" orientation="portrait"> </boxed-text> We demonstrate that mutant huntingtin (mHtt) binds to brain synaptic and nonsynaptic mitochondria and the amount of mitochondria‐bound mHtt correlates with increased mitochondrial Ca2+ uptake capacity. We propose that this may happen due to mHtt‐mediated sequestration of free fatty acids thereby increasing resistance of mitochondria to Ca2+‐induced damage.